Adaptive Statistical Iterative Reconstruction-V: Impact on Image Quality in Ultralow-Dose Coronary Computed Tomography Angiography. Issue 6 (November 2016) - Benz, Dominik C.; Gräni, Christoph; Mikulicic, Fran; Vontobel, Jan; Fuchs, Tobias A.; Possner, Mathias; Clerc, Olivier F.; Stehli, Julia; Gaemperli, Oliver; Pazhenkottil, Aju P.; Buechel, Ronny R.; Kaufmann, Philipp A.
Abstract : Objective: The clinical utility of a latest generation iterative reconstruction algorithm (adaptive statistical iterative reconstruction [ASiR-V]) has yet to be elucidated for coronary computed tomography angiography (CCTA). This study evaluates the impact of ASiR-V on signal, noise and image quality in CCTA. Methods: Sixty-five patients underwent clinically indicated CCTA on a 256-slice CT scanner using an ultralow-dose protocol. Data sets from each patient were reconstructed at 6 different levels of ASiR-V. Signal intensity was measured by placing a region of interest in the aortic root, LMA, and RCA. Similarly, noise was measured in the aortic root. Image quality was visually assessed by 2 readers. Results: Median radiation dose was 0.49 mSv. Image noise decreased with increasing levels of ASiR-V resulting in a significant increase in signal-to-noise ratio in the RCA and LMA ( P < 0.001). Correspondingly, image quality significantly increased with higher levels of ASiR-V ( P < 0.001). Conclusions: ASiR-V yields substantial noise reduction and improved image quality enabling introduction of ultralow-dose CCTA.